Estimating Smart Grid’s Carbon Emission Reduction Potential in China’s Manufacturing Industry Based on Decomposition Analysis - Fu, Hua; Shi, Yingying; Zeng, Yongchao (Frontiers in Energy Research, 2021)
There is a direct link between smart grid and carbon emissions. By leveraging distributed energy resources, smart grids can significantly reduce energy consumption and carbon emissions. As the largest emitter of CO2 dioxide, the manufacturing industry shoulders the important responsibility of emissions reduction in China. This paper implies temporal logarithmic mean divisia index (LMDI) method to analyze the driving forces of the CO2 emissions change of manufacturing industry of China from perspectives of the industry and 28 sub-industries from 2000 to 2017. The main conclusions reveal that industrial activity and energy intensity are the main factors that lead to the increase and mitigation of CO2 emissions respectively. Due to the high proportion of electric power in the energy structure of manufacturing industry, it is necessary to develop smart grid to reduce the proportion of coal in the energy structure and increase the proportion of renewable energy. Smart grid can reduce energy consumption and carbon emissions in power transmission, and promote green development of manufacturing industry.